An extracellular polysaccharide is involved in the aluminum tolerance of Pullulanibacillus sp. CA42, a newly isolated strain from the Chinese water chestnut growing in an actual acid sulfate soil area in Vietnam - Aizawa, Tomoko; Sato, Junki; Saito, Shimon; Yasuda, Takanari; Maruyama, Yutaro; Urai, Makoto (Frontiers in Microbiology, 2023)
A novel aluminum-tolerant bacterial strain CA42 was isolated from the aquatic plant Eleocharis dulcis, which grows in a highly acidic swamp in Vietnam. Inoculation with CA42 allowed Oryza sativa to grow in the presence of 300 μM AlCl3 at pH 3.5, and biofilms were observed around the roots. Using 16S rRNA gene sequencing analysis, the strain was identified as Pullulanibacillus sp. CA42. This strain secreted large amounts of an extracellular polysaccharide (CA42 EPS). Results from structural analyses on CA42 EPS, namely methylation analysis and nuclear magnetic resonance (NMR), indicated that the chemical structure of CA42 EPS was a glycogen-like α-glucan. Purified CA42 EPS and the commercially available oyster glycogen adsorbed aluminum ions up to 15-30 μmol/g dry weight. Digestion treatments with α-amylase and pullulanase completely attenuated the aluminum ion-adsorbing activity of purified CA42 EPS and oyster glycogen, suggesting that the glycogen-like structure adsorbed aluminum ions and that its branching structure played an important role in its aluminum adsorbing activity. Furthermore, the aluminum tolerance of CA42 cells was attenuated by pullulanase treatment directly on the live CA42 cells. These results suggest that CA42 EPS adsorbs aluminum ions and is involved in the aluminum tolerance mechanism of Pullulanibacillus sp. CA42. Thus, this strain may be a potential plant growth-promoting bacterium in Aluminum-adsorbing extracellular polysaccharide 2 acidic soils. In addition, this study is the first to report a glycogen-like polysaccharide that adsorbs aluminum ions.